Prolonged survival after disseminated Rhinocladiella infection treated with surgical excision and posaconazole. Issue 2 (26th February 2020) - Hardman, Nicola; Young, Nicola; Hobson, Richard; Sandoe, Jonathan; Wellberry‐Smith, Matthew; Thomson, Simon; Barton, Richard
Abstract: Cerebral abscess due to pigmented molds is a rare but usually fatal infection occasionally seen in transplant recipients. A 67‐year‐old man of Iraqi origin underwent a deceased donation renal transplant for renal failure and 2 months later was diagnosed with an abscess in the left posterior frontal lobe of his brain. Subsequent biopsy proved this to be due to the mold Rhinocladiella mackenziei. Further interventions included two operations to aspirate the lesion, voriconazole, then liposomal amphotericin B, then a combination of posaconazole and flucytosine which he continued for over 4 years. He also suffered from right ankle pain and was diagnosed with septic arthritis; R mackenziei was isolated from pus aspirated from the ankle joint. He responded well to the treatment and has had little loss of function, and on CT, the cerebral lesion has stabilized. Beta‐D‐glucan, initially at very high levels proved useful to monitor response over the 5 years and the latest sample was negative (38 pg/mL). This case is notable for the first disseminated case of this infection, its favorable outcome on a novel antifungal combination and a new approach to monitoring the course of disease.